Microwave-assisted co-pyrolysis of brown coal and corn stover for oil production. (July 2018) - Zhang, Yaning; Fan, Liangliang; Liu, Shiyu; Zhou, Nan; Ding, Kuan; Peng, Peng; Anderson, Erik; Addy, Min; Cheng, Yanling; Liu, Yuhuan; Li, Bingxi; Snyder, John; et al.
Highlights: Microwave-assisted co-pyrolysis of brown coal and corn stover was studied. Synergistic effects on oil yield and compositions were evaluated. Effects of CS/BC ratio and pyrolysis temperature were analyzed. Positive synergistic effect on oil yield was observed at 0.33 and 600 °C. Synergistic effects on oil compositions may be positive or negative. Abstract: The controversial synergistic effect between brown coal and biomass during co-pyrolysis deserves further investigation. This study detailed the oil production from microwave-assisted co-pyrolysis of brown coal (BC) and corn stover (CS) at different CS/BC ratios (0, 0.33, 0.50, 0.67, and 1) and pyrolysis temperatures (500, 550, and 600 °C). The results showed that a higher CS/BC ratio resulted in higher oil yield, and a higher pyrolysis temperature increased oil yield for brown coal and coal/corn mixtures. Corn stover and brown coal showed different pyrolysis characteristics, and positive synergistic effect on oil yield was observed only at CS/BC ratio of 0.33 and pyrolysis temperature of 600 °C. Oils from brown coal mainly included hydrocarbons and phenols whereas oils from corn stover and coal/corn mixtures were dominated by ketones, phenols, and aldehydes. Positive synergistic effects were observed for ketones, aldehydes, acids, and esters whereas negative synergistic effects for hydrocarbons, phenols and alcohols.